Ultrasound‐assisted prompted voiding for management of urinary incontinence of nursing home residents: Efficacy and feasibility. (11th July 2016) - Suzuki, Motofumi; Iguchi, Yasuhiro; Igawa, Yasuhiko; Yoshida, Mikako; Sanada, Hiromi; Miyazaki, Hideyo; Homma, Yukio
Abstract : Objectives: To assess the efficacy and feasibility of ultrasound‐assisted prompted voiding for the management of urinary incontinence in nursing homes. Methods: Nursing home residents who had received prompted voiding care for urinary incontinence were enrolled. The voided urinary volume and residual urinary volume were initially measured for a few days. The sum of the mean values of these volumes was considered as the optimal intravesical urinary volume for voiding. Thereafter, the participants underwent regular monitoring of intravesical urinary volume using an ultrasound device, and were prompted to void in a toilet when the monitored volume almost reached the optimal volume. The primary outcome for efficacy was the change in the absorbent cost before and after ultrasound‐assisted prompted voiding care over 12 weeks. The feasibility was assessed by the change in activity of daily living of residents and quality of life measures of the care workers. Results: A total of 77 residents completed the 12‐week ultrasound‐assisted prompted voiding intervention. The absorbent cost decreased in 40 participants (51.9%), and the overall cost decreased by 11.8% from the baseline value ( P = 0.006). The activity of daily living did not significantly change. The quality of life of the care workers significantly improved for subscales of role emotional ( P = 0.020) and mental health ( P = 0.007). Conclusions: The management of urinary incontinence for nursing homes residents through ultrasound‐assisted prompted voiding seems to reduce the absorbent cost and to partially improve care workers' quality of life.